2017
DOI: 10.1515/enr-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional asymmetry in the neurovisceral communication for the cardiovascular control: New insights

Abstract: Th e cardiovascular control involves a bidirectional functional connection between the brain and heart. We hypothesize that this connection could be extended to other organs using endocrine and autonomic nervous systems (ANS) as communication pathways. Th is implies a neuroendocrine interaction controlling particularly the cardiovascular function where the enzymatic cascade of the renin-angiotensin system (RAS) plays an essential role. It acts not only through its classic endocrine connection but also the ANS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
4
3
0
Order By: Relevance
“…It is necessary to take into account that functional asymmetries must have neurochemical substrates that support them and for this, neurochemical studies in experimental animals are essential, which may provide valuable information that cannot be approached with studies on humans, but for the moment it is hard to interpret. With the results of the present investigation, and also based on our previous studies [1,26], we can confirm that cerebral asymmetry is not a static but a dynamic concept, which is modifiable in the face Interestingly, the previous study of mean values [5], also showed no intra-and interhemispheric differences for LDH. In conclusion, the intra-and inter-hemispheric functionality of the LeuAP of the right frontal cortex, and consequently that of its substrates, presents greater heterogeneity than that of the left frontal cortex.…”
Section: Discussionsupporting
confidence: 88%
“…It is necessary to take into account that functional asymmetries must have neurochemical substrates that support them and for this, neurochemical studies in experimental animals are essential, which may provide valuable information that cannot be approached with studies on humans, but for the moment it is hard to interpret. With the results of the present investigation, and also based on our previous studies [1,26], we can confirm that cerebral asymmetry is not a static but a dynamic concept, which is modifiable in the face Interestingly, the previous study of mean values [5], also showed no intra-and interhemispheric differences for LDH. In conclusion, the intra-and inter-hemispheric functionality of the LeuAP of the right frontal cortex, and consequently that of its substrates, presents greater heterogeneity than that of the left frontal cortex.…”
Section: Discussionsupporting
confidence: 88%
“…Although correlation does not necessarily imply causation, this may be suggestive of a relationship between variables. Therefore, the present results together with previous ones, may reflect an asymmetrical bidirectional connection between brain and the rest of the organism, presumably mediated by the ANS [4,31,32].…”
Section: Discussionsupporting
confidence: 82%
“…Depression, for example, is a biopsychosocial condition that often co-occurs with physical health issues (Sanna et al, 2013) and is influenced by social norms (Mahalik, 2008), emphasizing the importance of examining intersections between the physiological and psychological. Recent medical research now identifies depression as an independent, primary risk factor for coronary disease (Cohen et al, 2015;Fioranelli et al, 2018;Lichtman et al, 2014), highlighting the bidirectional path between the neuroendocrine and cardiac systems (Prieto et al, 2017). Furthermore, there is an important behavioral pathway by which depression may contribute to heart disease which posits that health risk behaviors serve as coping strategies for managing negative affect connected to stress and other mental health concerns like depression (Folkman & Lazarus, 1986;Wills & Shiffman, 1985).…”
Section: The Head and The Heart: Psychological Factors In Cardiac Hea...mentioning
confidence: 99%